2024
DOI: 10.1371/journal.pone.0298145
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Arabic version of the perceived prosthodontic treatment need scale: Exploratory and confirmatory factor analyses

Rayan Sharka

Abstract: Background It is crucial to take into account the concerns of dental patients about their prosthodontic needs when planning the course of treatment. However, there is a dearth of research that examines these needs among adult dental patients. Objectives This study aims to translate and validate the perceived prosthodontic treatment need scale (PPTN) in Arabic. Methods The 17-item PPTN scale was translated from English into Arabic and completed by 206 patients seeking prosthodontic treatment in a dental hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(87 reference statements)
1
0
0
Order By: Relevance
“…This result was in line with a previous study conducted in Malysia that found that implementing pricing strategies may effectively influence patients' behavioral intentions in a positive manner (14). A significant proportion of the population in several countries is unable to afford dental healthcare as a result of the escalating expenses associated with dental materials and operations, compelling dentists to increase their rates (37,38). Due to the exorbitant expenses associated with dental treatment, patients might seek treatment from public hospitals (39).…”
Section: Discussionsupporting
confidence: 85%
“…This result was in line with a previous study conducted in Malysia that found that implementing pricing strategies may effectively influence patients' behavioral intentions in a positive manner (14). A significant proportion of the population in several countries is unable to afford dental healthcare as a result of the escalating expenses associated with dental materials and operations, compelling dentists to increase their rates (37,38). Due to the exorbitant expenses associated with dental treatment, patients might seek treatment from public hospitals (39).…”
Section: Discussionsupporting
confidence: 85%